How Spanish Grew. - Spaulding, Robert K. (Berkeley : University of California Press, 2022)
This book traces the evolution of the Spanish language from pre-Roman days to the present and stresses the influence of social and political events on its development. After a short discussion of the Indo-European tongues, Spaulding reviews the effects on Spanish of the languages of the pre-Roiman invaders, the Visigoths and other Germanic tribes, and the Arabs. The later development of Spanish is divided into four periods: Old Spanish (to 1500), Spanish Ascen.
Description based upon print version of record.
JSTOR
Keywords: Spanish language -- History; Espagnol (Langue) -- Histoire; Spanish language; History